Bioinspired synthesis of magnetite nanoparticles. (7th July 2016) - Mirabello, Giulia; Lenders, Jos J. M.; Sommerdijk, Nico A. J. M.
Abstract : Magnetite (Fe3 O4 ) is a widespread magnetic iron oxide encountered in many biological and geological systems, and also in many technological applications. Abstract : Magnetite (Fe3 O4 ) is a widespread magnetic iron oxide encountered in many biological and geological systems, and also in many technological applications. The magnetic properties of magnetite crystals depend strongly on the size and shape of its crystals. Hence, engineering magnetite nanoparticles with specific shapes and sizes allows tuning their properties to specific applications in a wide variety of fields, including catalysis, magnetic storage, targeted drug delivery, cancer diagnostics and magnetic resonance imaging (MRI). However, synthesis of magnetite with a specific size, shape and a narrow crystal size distribution is notoriously difficult without using high temperatures and non-aqueous media. Nevertheless, living organisms such as chitons and magnetotactic bacteria are able to form magnetite crystals with well controlled sizes and shapes under ambient conditions and in aqueous media. In these biomineralization processes the organisms use a twofold strategy to control magnetite formation: the mineral is formed from a poorly crystalline precursor phase, and nucleation and growth are controlled through the interaction of the mineral with biomolecular templates and additives. Taking inspiration from this biological strategy is a promising route to achieve control over the kinetics of magnetite crystallization under ambient conditions and in aqueous media. In this review we first summarize the main characteristics of magnetite and what is known about the mechanisms of magnetite biomineralization. We then describe the most common routes to synthesize magnetite and subsequently will introduce recent efforts in bioinspired magnetite synthesis. We describe how the use of poorly ordered, more soluble precursors such as ferrihydrite (FeH) or white rust (Fe(OH)2 ) can be employed to control the solution supersaturation, setting the conditions for continued growth. Further, we show how the use of various organic additives such as proteins, peptides and polymers allows for either the promotion or inhibition of magnetite nucleation and growth processes. At last we discuss how the formation of magnetite-based organic–inorganic hybrids leads to new functional nanomaterials.